Celebrate her for the fruit of her hands essays in honor of Carol L. Meyers - Meyers, Carol L. 1942-; Ackerman, Susan 1958- (Winona Lake, Indiana Eisenbrauns, 2014)
Contents -- Preface -- Abbreviations -- A Select Bibliography of the Works of Carol L. Meyers -- Introduction: A Teacher and Scholarâ€?s Appreciation -- Charles E. Carter -- Introduction: A Colleagueâ€?s Appreciation -- Susan Ackerman -- Hannahâ€?s Tears -- Susan Ackerman -- Women, Law, and Legal Procedure in Ancient Israel -- James P. Ashmore -- Nationalist Narratives and Biblical Memory -- Cynthia M. Baker -- When It Both Is and Is Not Rape: Gender Constructions in 2â€S̄amuel 13:1â€?22 -- Karla G. Bohmbach
Speaking as â€œAny Foolish Womanâ€?: Ms. Job in the History of ReceptionRhonda Burnette-Bletsch -- Numbers 5:11â€?31 -- Women in Second Temple Judah and the Law of the Controlling Priest -- Claudia V. Camp -- â€œThere Is Much Wisdom in Herâ€?: The Matriarchs in the Qumran Library -- Sidnie White Crawford -- Poor but Wise (Qoheleth 9:13â€?16) -- James L. Crenshaw -- Reading the Bible as Agrarian Literature -- Ellen Davis -- Israelite Women as â€œRitual Expertsâ€?: Orthodoxy or Orthopraxis? -- William G. Dever
Structure and Origin of the Early Israelite and Iroquois ConfederaciesNorman K. Gottwald -- The Place of Biblical Studies in the University Curriculum -- Beyond the Religious/Secular Divide -- Sandie Gravett -- Bargaining with Patriarchy in the Book of Ruth -- F. V. Greifenhagen -- Gendered Sectarians: Envisioning Women (and Men) at Qumran -- Maxine L. Grossman -- Translating Women -- The Perils of Gender-Inclusive Translation of the New Testament -- Ross S. Kraemer and Jennifer Eyl -- Ethnicity, Culture, and Religion in Artifact and Text
The Emergence of Complex Common JudaismEric M. Meyers -- Plaque Figurines and the Relationship between Canaanite and Egyptian Women in the Late Bronze II -- Beth Alpert Nakhai -- The Story of David and Goliath from the Perspective of the Study of Oral Traditions -- Raymond F. Person Jr. -- I Sing the Body Politic: Stillborn Desire and the Birth of Israel in Judges 5 -- Anathea Portier-Young
Includes bibliographical references and indexes. - Description based on print version record and CIP data provided by publisher; resource not viewed
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Meyers, Carol L -- Meyers, Carol L; Meyers, Carol L; Bible -- Feminist criticism; Bible -- Criticism, interpretation, etc -- Bible -- Bible; Bible -- Feminist criticism; Bible -- Criticism, interpretation, etc; Bible; Women in the Bible; Bible and feminism; BIBLES ; General; RELIGION ; Biblical Reference ; General; RELIGION ; Biblical Reference ; Handbooks; Feminist Criticism; Criticism, interpretation, etc; Electronic books -- Criticism, interpretation, etc; Festschrift